HUBUNGAN ANTARA DERAJAT HIPERTENSI DENGAN MEKANISME KOPING PENDERITA HIPERTENSI - Andriyanto, Arief; Santoso, Windu (JURNAL KEPERAWATAN SEHAT, 2015)
Adrenal hormones can stimulate the heart beat stronger and faster until eventually lead to increased blood pressure. One of the ways by individuals to cope with the stress they face called coping mechanism. The destination objective was to determine the relationship between the degree of hypertension in coping mechanism patients hypertensi in Poly Medicine Hospital of Islam Sakinah Mojokerto. Corelational analytic study design with cross sectional approach. All the client population of patients hypertensi in Poly Disease Hospital Islam Sakinah Mojokerto in March 2013 to obtain a sample of 33 people who were taken with consecutive sampling. Independent variables degrees of hypertension and the dependent variable hypertensi coping mechanisms. Data collected by observation using stetoscope and tension and questionare. Having collected the data processing is done and followed by statistical test Chi Square with a significant level of 0.05 using SPSS 16 for windows. The results showed ρ = 0.016 <0.05 then H1is accepted or H0rejected means there is a relationship between the degree of hypertension in coping mechanism patients hypertensi in Islamic Hospital Sakinah Mojokerto. Patients with hypertension is expected to increase the knowledge and use of adaptive coping when it is having problems. Hospitals may be providing input on the coping mechanisms of hypertensi patients in the hospital so that the nurse can provide counseling and appropriate health education for patients with hypertension.Keywords: degree of hypertension, coping mechanisms